Do market, resource and knowledge distance impact inbound cross-border acquisition? - Mohammad Abedin (Global Finance Journal, 2023)
With the increasing phenomena of cross-border acquisition (CBA) activities in emerging economies (EE), evidence about “distance” factors that make these economies attractive to home country firms is sparse. Given this background, we employ major locational advantage distance measures such as market, resource, and knowledge distances and examine their impact on the value and number of inbound CBAs in India. We source inbound CBA deal data from the Thomson Reuters Eikon database for the 1990–2020 period during which 47 home countries were making acquisitions of targets in India. We develop relevant hypotheses based on a literature review. We run tobit and negative binomial regression models on a final sample of 921 country-pair-year observations to test the hypotheses. The results show that increasing market and knowledge distances enhanced the value and number of India's inbound CBAs, fueled by the country's growth potential and knowledge base. However, we find no evidence of a role played by resource distance.